2019
DOI: 10.1172/jci133117
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diarrhea, bile acids, and Clostridia

Abstract: Excessive fecal bile acid (BA) loss causes symptoms in a large proportion of people diagnosed with irritable bowel syndrome with diarrhea, a common functional bowel disorder. This bile acid diarrhea (BAD) results from increased hepatic synthesis of BAs, with impaired negative feedback regulation by the ileal hormone fibroblast growth factor 19 (FGF19). In this issue of the JCI, Zhao et al. investigated BA metabolism, including fecal BAs, serum BAs and FGF19, in patients and controls. They identified associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Indeed, whereas patients with IBS-D have a higher proportion of Escherichia coli and decreased Clostridium leptum and Bifidobacterium (40), a recent report showed that 24.5% of patients with IBS-D exhibited excessive excretion of total BAs and increase in Clostridia bacteria (e.g., C. scindens), which was positively associated with the levels of fecal BAs and serum 7α-hydroxy-4-cholesten-3-one (C4) (41). The latter finding suggested that Clostridia bacteria have potential as a biomarker for BAD and as a target for therapy (42), although this still requires formal testing in humans.…”
Section: Mechanisms Leading To Gastrointestinal Symptoms In Bile Acid Malabsorptionmentioning
confidence: 94%
“…Indeed, whereas patients with IBS-D have a higher proportion of Escherichia coli and decreased Clostridium leptum and Bifidobacterium (40), a recent report showed that 24.5% of patients with IBS-D exhibited excessive excretion of total BAs and increase in Clostridia bacteria (e.g., C. scindens), which was positively associated with the levels of fecal BAs and serum 7α-hydroxy-4-cholesten-3-one (C4) (41). The latter finding suggested that Clostridia bacteria have potential as a biomarker for BAD and as a target for therapy (42), although this still requires formal testing in humans.…”
Section: Mechanisms Leading To Gastrointestinal Symptoms In Bile Acid Malabsorptionmentioning
confidence: 94%
“…For example, patients whose main biological disturbance is robust deconjugation of primary bile acids may benefit from a BSH inhibitor 40 or cholylsarcosine, 41 whereas those patients who do not convert primary to secondary bile acids may benefit from bile acid binding resins like cholestyramine or targeted engraftment of Clostridia species. 42 Indeed, our findings provide evidence for the potential value of the gut microbiome and its co-metabolites as a prognostic platform for precision nutrition and other therapeutic strategies in patients with SBS. Such a paradigm may have relevance to other diseases such as intestinal motility disorders associated with SIBO and environmental enteric dysfunction where alterations in the small intestinal microbiota have been described.…”
Section: Discussionmentioning
confidence: 69%
“…En un estudio en el que se realizó el análisis metagenómico y metabolómico en 290 pacientes con SII-D y 89 voluntarios sanos, se observó que el incremento de clostridiales se asoció positivamente con los niveles de AB en heces y 7αC4 sérico, con disminución de los niveles de FGF19 60 . El rol de los clostridiales en la disminución de la transformación de AB y su importancia en la patogénesis del SII-D necesita ser replicado, pero abre una puerta al tratamiento antibiótico en estos pacientes 61 .…”
Section: Exceso De áCidos Biliares En La Diarrea Funcional Y El Sii-d...unclassified